Dosis de aceite rojo de palma en la salud intestinal y rentabilidad económica de pollos Cobb 500 en Zúngarococha durante el año 2024 - Peña Gonzales, Jhon Pool Javier (2025)
The use of natural additives such as red palm oil represents a strategic alternative in poultry production, promoting physiological and productive improvements without the use of synthetic promoters. The general objective was to determine the effect of red palm oil doses on stool consistency, feed conversion and profitability in Cobb 500 chickens. A completely randomized design (DCA) was used with five treatments: T0 (0%), T1 (0.5%), T2 (1%), T3 (1.5%), and T4 (2%), with four replicates per treatment. Productive variables (weight, gain, conversion and feed efficiency), physiological (fecal consistency) and economic (costs, income and profitability) were evaluated. The results indicated that birds treated with 1.5% (T3) and 2% (T4) red palm oil presented the best responses in final weight (2390.9 g and 2319.2 g, respectively), weight gain (1832.8 g and 1762.6 g) and profitability (24.00% and 20.83%). There was also a significant positive correlation between dose and stool consistency (r = 0.93, p < 0.001), indicating a laxative effect with greater inclusion. It is concluded that the inclusion of up to 1.5% red palm oil improves zootechnical and economic performance, without compromising intestinal health. It is recommended to delve into studies with lower levels and combinations with other natural additives to optimize their effect.